B2.1 100, 000 genomes project at gosh: experience from 111 pilot families. (4th October 2017) - Clement, E; Buckton, A; Ashton, E; Scott, R; Beales, P; Loughlin, S; Bitner-Glindzicz, M; Jenkins, L
Abstract : Background: The 100, 000 Genomes Project is a national programme to perform whole genome sequencing (WGS) in families with an undiagnosed rare disorder or cancer. Multiple specialties from GOSH have recruited patients to the pilot study. Here we report on the outcome of the first 111 pilot cases. Methodology: Total lymphocyte DNA was extracted (Chemagic Star, Chemagen) and exported to Genomics England for WGS (HiSeqX, Illumina). Prioritised variants were discussed and classified by a multidisciplinary team (MDT) of Clinical Scientists, Consultant Clinical Geneticists and the recruiting clinicians. Variants deemed to be 'pathogenic' or 'likely pathogenic' were flagged for diagnostic confirmation and clinical reporting. Results: Genomics England returned results for 111 cases (probands); 95 (86%) were analysed as trios (proband and both parents). Variant interpretation has been completed for 97 cases (87%). Thirty-six percent of cases (40/111) and a total of 76 variants were discussed at an MDT meeting. Fifty-three percent of variants discussed (40/76) were classified as pathogenic or likely pathogenic, 30% (23/76) were classified as variants of unknown significance and 17% (13/76) were classified as benign or likely benign. This equated to a genetic diagnosis in 27/111 cases (25%) of which 5/111 (5%) were felt to be a partial rather than full explanation of the phenotype. Of the 97 cases where primary analysis was complete, 66/97 (68%) had no primary findings. This included cases in which variants of unknown significance have been detected. Conclusion: WGS is a useful tool for rare disease diagnosis especially in patients who have undergone a fruitless diagnostic odyssey. Analysis of GOSH pilot cases has enabled us to develop infrastructure locally to support the return of main programme results. One quarter of GOSH pilot patients should expect a genetic diagnosis from the primary analysis. It is unclear whether this will be an accurate reflection of the diagnostic rate achieved in the main programme due to ongoing refinement of the recruitment and analysis pipelines.